Characterization of recombinant cutinase from Thermobifida cellulosilytica and its application in tomato cutin degradation. (January 2023) - Jiddah Usman, Nafiu; Rodrid, Kanyarat; Sabo Ajingi, Ya'u; Tuncharoen, Natthida; Meegnoen, Kunlasatri; Pason, Patthra; Jongruja, Nujarin
Abstract: Cutinases are desirable biorecycling agents for big molecules because of their great efficiency in generating monomer under mild reaction conditions. In this study, the biochemical characterizations of a thermostable cutinase from Thermobifida cellulosilytica for tomato cutin degradation are presented. The cutinase gene was chosen from the sequence database. The gene was synthesized, cloned, and successfully expressed in the Escherichia coli ( E. coli ) system. SDS-PAGE analysis revealed that the cutinase had a molecular weight of approximately 29kDa. The recombinant cutinase showed highest activity at an optimum pH of 9.0. The result also showed thermal stability up to 60 °C. The activity of the recombinant cutinase was enhanced by 1 mM NaCl, 5 mM NaCl and 1 mM CaCl2 ; however, slightly inhibited by 5 mM CaCl2 . Cutin from tomato peel was efficiently degraded into free fatty acid monomers. The bonding features between the deteriorated and polymerized cutin were clearly visible in the fourier transformed infrared spectroscopy study. These findings open the possibilities of using cutinases for the generation of free fatty acids from tomato peel. It could be a potential raw material for other industrial applications. Highlights: The recombinant thermostable cutinase showed optimum activity at a pH of 9.0 The recombinant thermostable cutinase has thermal stability up to 60 °C. The recombinant cutinase degrades tomato cutin into free fatty acids. FTIR analysis shows distinct bond difference between the polymerized tomato cutin and degraded cutin.